Difficulties and challenges in the learning process of algorithms and programming in higher education: a systematic literature review (Research, Society and Development, 2020)
Learning to program is often a challenge for students: each student has their individual difficulties and teachers need to identify them in order to provide the necessary support to their students. In this sense, this article presents part of the results obtained in a Systematic Literature Review on the process of learning algorithms and programming. The main objective of the work presented here is to point out the main difficulties and challenges experienced by higher education students in Algorithms and Programming disciplines, as well as what these difficulties can bring to students along their academic path. The choice of the research method was because the Systematic Literature Review presents a type of study whose methodology is well defined, being able to evaluate the research in a careful, reliable and objective way. For this study, the review was conducted in four databases: Web of Science, Scopus, IEEE Xplore and RCAAP. For that, a review question was defined, the keywords, the necessary equation for the study, as well as the review protocol. Initially, 350 articles were found, of which 169 articles were pre-selected. After applying the inclusion and exclusion criteria, 33 articles were selected for the analysis and development of this work. With the analysis, we were able to verify and categorize the difficulties and challenges faced by students during the process of learning algorithms and programming. With the results presented, this article can contribute with an overview capable of serving as a starting point for other research, as well as to assist teachers and students in the perception of these difficulties.